2022
DOI: 10.1097/mcc.0000000000000980
|View full text |Cite
|
Sign up to set email alerts
|

Critical care management of meningitis and encephalitis: an update

Abstract: Purpose of reviewMeningitis and encephalitis represent severe neurological syndromes associated with encephalopathy, seizures, focal deficits, and neurological sequelae in survivors. We update on the critical care management of adult patients with severe meningitis and encephalitis.Recent findingsLarge multicenter studies conducted in the adult population improved current knowledge on the epidemiology and outcomes of patients with severe meningitis and encephalitis. An early multimodal diagnostic workup (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Recently, increasing evidence suggested that immunotherapy might be an attractive strategy for the treatment in ICU 4 , 5 . Both innate and adaptive immunity are dysregulated during the progression of critical illness 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, increasing evidence suggested that immunotherapy might be an attractive strategy for the treatment in ICU 4 , 5 . Both innate and adaptive immunity are dysregulated during the progression of critical illness 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, coma remains one of the most frequent reasons for admission to intensive care. Status epilepticus [1,2] and autoimmune encephalitis [3] are undoubtedly the neuro-critical care pathologies which have attracted the most interest in recent years.…”
mentioning
confidence: 99%